Real option valuation using Weibull distribution: a new framework for depreciation risk management - Ko, Seok Bin (Seonmul yeongu (Online), 2025)
This study aims to develop an accurate option pricing model for car leases by introducing a put option valuation framework based on the Weibull distribution. Traditional models typically assume asset values follow a lognormal distribution, failing to capture the left-skewed nature and bounded dynamics. To address this limitation, this study compares the performance of the Weibull distribution with that of the lognormal model using residual value data from two popular car models in South Korea, evaluating each model’s ability to reflect unique depreciation patterns. The findings demonstrate that the Weibull distribution provides a superior fit to the data, leading to more precise option pricing. This enhanced accuracy is crucial for auto finance companies navigating uncertainties in used car prices, particularly as the mobility services and car leasing markets continue to expand. Moreover, the practical implications of this research extend beyond the auto finance industry; insights from this study can inform sectors dealing with skewed or bounded assets, such as insurance products and financial derivatives, thereby enabling improved risk assessment and decision-making processes. This research introduces a novel approach to modeling put option values using the Weibull distribution, filling a significant gap in the existing literature on car lease option pricing. However, as this is the first study to model put option values using the Weibull distribution, further research is necessary. Specifically, investigating volatility patterns over the lifecycle of used cars could significantly enhance the value of this framework.